Clinical epidemiological characterization of patients with type II diabetes mellitus - Tania Leyva Miranda; Mayelín Masmout Gil; Isabel Cristina Carbonel; Donelia Gámez Sánchez; Odeite Dueñas Moreira (Centro Provincial de Información de Ciencias Médicas, 2017)
An observational, descriptive and cross-sectional study of 700 patients with type II diabetes mellitus, assisted in "Julián Grimau García" and "Carlos Juan Finlay" health areas was carried out in Santiago de Cuba during 2014, aimed at characterizing them according to clinical-epidemiological variables of interest. In the series there was a prevalence of the female sex, 61 years and over age group, hypertension, obesity and the dyslipidemia as main comorbidities, besides the peripheral neuropathy, the peripheral vascular illness and the retinopathy as  more common complications. On the other hand, the used medications were the oral hypoglycemic agents and it was identified the risk of metabolic complications, tabaquism and alcohol consumption; this last doubled in the male sex.